Four new species and eighteen lectotypifications of Larnax from Ecuador and Peru and a new synonym of Deprea orinocensis (Solanaceae: Solanoideae, Physalideae) - Deanna, Rocío; González, Segundo Leiva; Barboza, Gloria E. (Phytotaxa, 2014)
Four new species of Larnax, L. macasiana, L. pumila, L. purpureocarpa, and L. toledoana, are described and illustrated and species conservation assessments presented. Eighteen lectotypifications of Peruvian Larnax: Larnax abra-patriciae, L. altomayoensis, L. bongaraensis, L. chotanae, L. dilloniana, L. kann-rasmusseniorum, L. longipedunculata, L. lutea, L. nieva, L. pedrazae, L. peruviana, L. pilosa, L. pomacochaense, L. purpurea, L. sagasteguii, L. sawyeriana, L. schjellerupiae, and L. vasquezii are proposed, mostly to replace material destroyed in a fire at HAO (Trujillo, Peru). A new synonym of Deprea orinocensis from Ecuador, Iochroma suffruticosum is also proposed and lectotypified based on an examination of original type material.